Barter and Monetary Exchange Under Private Information - Williamson, Steve; Wright, Randall (American Economic Review, 1994)
We develop a model of production and exchange with uncertainty concerning the quality of commodities and study the role of fiat money in ameliorating frictions caused by private information. The model is specified so that, without private information, only high-quality commodities are produced, and there is no welfare gain from using money. With private information, there can be equilibria (and sometimes multiple equilibria) where low-quality commodities are produced, and money can increase welfare. Money works by promoting useful production and exchange. In efficient monetary equilibria, agents adopt strategies that increase the probability of acquiring high-quality output.